Luminescence of Agrotextiles Based on Red-Light-Emitting Organic Luminophore and Polypropylene Spunbond Enhances the Growth and Photosynthesis of Vegetable Plants - Khramov, Robert; Kosobryukhov, Anatoly; Kreslavski, Vladimir; Balakirev, Dmitry; Khudyakova, Alexandra; Svidchenko, Evgeniya; Surin, Nikolay; Ponomarenko, Sergey; Luponosov, Yuriy (Frontiers in Plant Science, 2022)
The impact of a light-transforming covering on photosynthetic activity and growth processes in lettuce and white cabbage plants grown in a glass greenhouse was studied. Plants were covered with agrotextile, a polypropylene (PP) nonwoven spunbond coated with polylactide varnish containing a new organic luminophore (LUM), which absorbs sunlight mainly in the 460–560 nm region and efficiently reradiates it in the red spectral region with a maximum at 660 nm. For comparison, simultaneously two references agrotextiles without LUM or containing a non-luminescent chromophore (ABS) with an absorption spectrum close to that of LUM were as well investigated. The use of the agrotextile with LUM resulted in a significant increase in total crude aboveground biomass for 32-, 33-, and 43-day-old plants on the average by 20–40%, and the photosynthesis rate increased on the average by 30–40% compared to the agrotextile without LUM. The use of the agrotextile with ABS mimicking the absorption of LUM also did not reveal a significant impact on photosynthesis and biomass accumulation in the plants as compared to the reference agrotextile coated only with the polylactide varnish. At the same time, the photosystem II activity (Fv/Fm and F′v/F′m quantum yields) was nearly the same in all experiments. When plants were grown under the light-converting agrotextile, the luminescent component of the converted light in the red spectrum region led to an increase in plant growth and photosynthesis rate, which is a fundamentally new result. Possible reasons for the stimulation of growth and photosynthesis due to the redistribution of the light spectral composition were analyzed. The use of covering materials containing luminophores similar to LUM can be promising in agrobiotechnology not only for green and vegetable crops but also for other field and greenhouse crops and various fruit bushes and trees.